2013
DOI: 10.1186/1471-2261-13-104
|View full text |Cite
|
Sign up to set email alerts
|

Early accelerated senescence of circulating endothelial progenitor cells in premature coronary artery disease patients in a developing country - a case control study

Abstract: BackgroundThe decreased number and senescence of circulating endothelial progenitor cells (EPCs) are considered markers of vascular senescence associated with aging, atherosclerosis, and coronary artery disease (CAD) in elderly. In this study, we explore the role of vascular senescence in premature CAD (PCAD) in a developing country by comparing the numerical status and senescence of circulating EPCs in PCAD patients to controls.MethodsEPCs were measured by flow cytometry in 57 patients with angiographically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…Our findings revealed that the levels of EPC, SDF‐1α, VEGF, and NO were decreased greatly in the elderly patients with multivessel reocclusions compared to the elderly patients with one‐ or two‐vessel reocclusions. Oxidative stress responses and inflammatory responses decreased the overexpressions of EPC, SDF‐1α, VEGF, and NO, and the reduced circulating EPC, SDF‐1α, VEGF, and NO led to coronary in‐stent restenosis . The present study suggested that the decreased levels of EPC, SDF‐1α, VEGF, and NO were related to coronary in‐stent reocclusion and severity of reocclusion after coronary stenting and may be considered as the important targets for treatment in a new stent design for interventional therapy of coronary artery stenoses.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Our findings revealed that the levels of EPC, SDF‐1α, VEGF, and NO were decreased greatly in the elderly patients with multivessel reocclusions compared to the elderly patients with one‐ or two‐vessel reocclusions. Oxidative stress responses and inflammatory responses decreased the overexpressions of EPC, SDF‐1α, VEGF, and NO, and the reduced circulating EPC, SDF‐1α, VEGF, and NO led to coronary in‐stent restenosis . The present study suggested that the decreased levels of EPC, SDF‐1α, VEGF, and NO were related to coronary in‐stent reocclusion and severity of reocclusion after coronary stenting and may be considered as the important targets for treatment in a new stent design for interventional therapy of coronary artery stenoses.…”
Section: Discussionmentioning
confidence: 51%
“…The enhanced oxidative stress shortened EPC telomeres and decreased EPC telomerase activity and promoted the reduced circulating EPCs in the patients with CHD. The research suggested that the significantly lower EPC number led to endothelial dysfunction and atherosclerosis in the patients with CHD . The studies also showed that the insufficient numbers of EPCs were related to coronary stenosis and severity of CHD, and the number of circulating EPCs was significantly lower in two and three vessel disease compared to single vessel disease in the patients with CHD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…31 Consistent with this view, several studies have used LTL as a marker of biological aging and have linked it to age-related diseases including atherosclerosis and its consequences, 32 such as peripheral vascular disease, 7, 33 CAD, 34 and importantly, cardiovascular mortality. 2, 32 Since aging is associated with decline in circulating PCs, and atherosclerosis is thought to develop as a result of an imbalance between endogenous repair mechanisms and factors causing cell injury, 35, 36 most of the studies have speculated that these observed clinical associations were related to decreased regenerative capacity. Increased inflammation and oxidative stress, two known key factors in the pathophysiology of atherosclerosis, 37 may result in increased utilization of circulating PCs, which home to the ischemic tissue and denuded endothelium to contribute to vascular and endothelial repair.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CAD significant telomere attrition can already be found in early stages of disease [14]. The difference in the telomere length attrition between PAD and CAD may also result from a much lower cellular turnover by the chronic inflammation of PAD compared to a much higher cellular turnover in CAD.…”
Section: Discussionmentioning
confidence: 99%